Factor Analysis of Passengers’ Satisfaction in Nigerian Airports - Ben, Sidiq Okwudili (American International Journal of Social Science Research, 2019)
This study determined complex factors influencing passengers’ satisfaction in Nigerian Airports. Theoretical evidence was examined and factor analysis was carried out to identify the main groups of factors affecting passengers’ satisfaction at the Airport. Primary data was gathered from domestic air passengers with random and systemic sampling techniques. 71.1 percent of questionnaires were retrieved from respondents in Lagos, and 61.9 percent of questionnaires were retrieved from respondents in Abuja. The findings of the study show that the most important five factors affecting it are: courtesy of staff, availability of staff, effective way finding signs, availability of telecommunications, and cleanliness of restrooms. The results obtained from this study will help airport managers in the Nigeria to better serve their passengers through improved attitudes of airport staff and improved technologies.